PENGARUH MEDIA PEMBELAJARAN BUSY BOOK TERHADAP TINGKAT PENGETAHUAN KARIES GIGI PADA SISWA KELAS III SEKOLAH DASAR - Nurazizah, Febriliany; Chaerudin, Denden Ridwan; Laut, Deru Marah; Supriyanto, Irwan (Poltekkes Kemenkes Bandung, 2025)
The breakdown of hard tooth tissue, or dental caries, is a common occurrence in elementary school students. This is because kids don't know enough about dental health. Learning can have an impact on a student's knowledge. Busy Book learning materials are one way to provide learning materials that can stimulate student interest and comprehension, which is why they are essential. The study aimed to ascertain how Busy Book learning materials affect third-grade students at SD Negeri 1 Kayuambon Lembang's level of dental caries knowledge. Pre-experimental research methodology was applied. There were 71 class III students in the study population. Purposive sampling was used to get 35 participants. Direct data collection from respondents took the form of a pretest-posttest. The dependent t-test results revealed that the p-value was 0.000. The results indicate that third grade students at SD Negeri 1 Kayuambon Lembang have a significantly different level of knowledge about dental caries when using the Busy Book learning media (p - value <0.05).